Globalisasi, Konstitusi dan Hak Asasi Manusia: Pengaruh Globalisasi terhadap Pengaturan HAM dalam Konstitusi Indonesia - Udiyo Basuki (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2013)
Globalization is a phenomenon that can not be avoided by anyone, any nation and any country, including Indonesia. It brings an enormous influence on aspects of national life, including the thought of human rights. The influence of the ideas and insights of global human rights reflected in the human rights debate setting on early days of the first constitution, the 1945 Constitution. In the reform era, the impact of thought globalization of human rights requires a constitutional amendment, which finally produced the regulation of human rights in the 1945 Constitution.